Language development in Slovenian toddlers: the role of electronic media, parental knowledge of language development, and parental input - Fekonja, Urška; Marjanovič-Umek, Ljubica; Pogorelc-Jesih, Nika; Ferjan Ramírez, Naja (Frontiers in Developmental Psychology, 2024)
IntroductionThis study examines the relationships between toddlers' language production, parental language input, media exposure, and parental knowledge of early language development.MethodsWe used a unique collection of daylong recordings of Slovenian toddlers (age: 16–30 months, N = 40, 18 girls) to measure the language environment, toddlers' language production and media exposure. In addition, parental reports of toddlers' media exposure and language ability (using the Slovenian adaptation of the CDI) were collected.ResultsThe results indicate that toddlers' average exposure to electronic media was rather low, with exposure varying widely across the sample. Parental language input was related to various measures of toddlers' language. Parents with a greater knowledge of early language development used more parentese, while their toddlers had less exposure to electronic media. In addition, toddlers' media exposure was related to their age, with older toddlers having more exposure to electronic media, and was marginally related to the number of words spoken by adults and parents' education. No significant relationship was found between toddlers' language ability and media exposure when controlling for toddlers' age.DiscussionThe findings underline the importance of parental knowledge about language development and the characteristics of the language environment for toddlers' language ability.